The Destination is where I Live! Residents’ Perception of Tourism Impacts - Renda, Ana Isabel; Mendes, Júlio da Costa; Valle, Patrícia Oom do (Journal of Tourism, Sustainability and Well-being, 2014)
The main purpose of this paper is to understand how residents perceive tourism impacts. Based on the review of the literature in the area of tourism, in particular with regard to its development and to the residents’ perceptions and attitudes towards this phenomenon, we studied the case of the municipality of Loulé, a privileged area of the tourist destination Algarve. The study adopts the residents’ point of view, a perspective still with much to explore when it comes to tourism. It analyses the relationship between variables such as the perception of social, economic, cultural and environmental impacts in people’s personal lives and in the area of residence, type and frequency of contact with tourism, professional and economic dependence on tourism and demographic characteristics. The results show that although residents identify, as the literature suggests, negative impacts of tourism, in general, they also acknowledge the importance of the tourism development in their area of residence and in their personal lives. It is noted that residents perceive tourism impacts differently according to professional and economic dependence on tourism activity, the proximity of the place of residence to the main tourist area and the frequency and type of contact with tourism. Demographic factors are not the most significant in explaining the perception of tourism impacts. The results of the study reinforce the importance of considering the residents’ perceptions vis-à-vis the tourism as a decisive factor in the sustainable development of tourism destinations, being thus residents one of the key stakeholders in the context of a holistic and integrated approach to tourism planning and development.